A randomized controlled study comparing oral misoprostol with intramuscular oxytocin in active management of third stage of labour - Atanda Abdulrasaq Sambo; Munir'deen Aderemi Ijaiya; Duum Nwachukwu; Ikemefuna Christopher Nwosu; Haruna Idris; Rasheedat Morayo Abdullateef; Folorunsho Benard Adewale (Korean Society of Obstetrics and Gynecology, 2024)
Objective The study aimed to compare the effectiveness and side effects of 600 μg of oral Misoprostol with 10 international units (IU) intramuscular oxytocin in managing the third stage of labor. Methods This open-label, randomized controlled trial included 260 low-risk women in the second stage of labor with anticipated vaginal delivery. They were randomly assigned, to receive either 600 μg of misoprostol orally or 10 IU of oxytocin intramuscularly. The primary outcomes were blood loss during delivery and incidence of postpartum hemorrhage, evaluated using intention-to-treat analysis. Significance was set at P≤0.05. Results Baseline characteristics were similar in both groups (P>0.05). The misoprostol group had a significantly lower blood loss than that of the oxytocin group (306.57±176.44 mL vs. 349.37±135.50 mL; relative difference, −12.251 [95% confidence intervals [CI], −22.528 to −1.575]; P=0.012). Incidence of postpartum hemorrhage was similar in both the groups (relative risk [RR], 0.952 [95% CI, 0.543 to 0.671]; P=0.865). Additional oxytocic therapy requirement was also comparable (RR, 1.143 [95% CI, 0.671 to 1.947]; P=0.623). Nausea, shivering, and mean increase in temperature were significantly more common in the misoprostol group than in the oxytocin-parturient group. Conclusion In this study, 600 μg oral misoprostol was superior to intramuscular 10 IU oxytocin in reducing blood loss at birth, and equally effective in preventing postpartum hemorrhage. However, misoprostol exhibited more side effects compared to that of oxytocin.